Polymer Nanocomposites Characterization: Atomic Layer Deposition of Metal Oxide on Nanocellulose for Enabling Microscopic Characterization of Polymer Nanocomposites (Small 46/2018). Issue 46 (15th November 2018) - Septevani, Athanasia A.; Evans, David A. C.; Hosseinmardi, Alireza; Martin, Darren J.; Simonsen, John; Conley, John F.; Annamalai, Pratheep K.
Abstract : Characterization of organic nanoparticle orientation in a polyurethane foam, which exhibits anisotropic mechanical properties, remains challenging. In article number1803439, John F. Conley Jr., Pratheep K. Annamalai, and co‐workers briefly demonstrate the application of atomic layer deposition to enhance the contrast of nanocellulose through a coating of alumina on nanocellulose and enabling microscopic characterisation. By incorporating alumina coated nanocellulose in a polyurethane foam, it also demonstrates nanocellulose alignment in the foam‐rise direction.